Tumor cell heterogeneity - Chekhun, V.F.; Sherban, S.D.; Savtsova, Z.D. (Experimental Oncology, 2013)
The paper deals with the analysis of literary data on the tumor cell heterogeneity. Phenotypic, genetic and epigenetic mechanisms of heterogeneity are considered. The heterogeneity or metastasis is considered too. The importance for the biology of populations of tumor cells and the sensitivity of tumors to therapeutic treatment are discussed. Key Words: primary tumor, metastasis, heterogeneity, malignant phenotype, genetic instability, epigenetic factors.